A emergência do saber gastronômico na academia: a experiência do bacharelado em gastronomia da Universidade Federal do Ceará - Brandão, Beatriz Helena Peixoto (2014)
This work aims, as a general objective, to discuss the formation of the Bachelor in gastronomy from the Federal University of Ceará, inserted in the Institute of Culture and Art, through the analysis of his political pedagogical project as well as through the speech of managers, professors and students concerning the experiences and impressions of the course. As specific objectives it aims to: a) document the creation of the holder of a Bachelor´s Degree in gastronomy and the experience of the first class to hold this degree from the UFC in the year 2013; b) to check curriculum trends of the course and their applications as a benchmark for the performance of the Bachelor; c) from the reconstitution of scenarios and experiences of an institution which is also in training, aided by reflection of respondents, to propose recommendations to actors who compound the course. The qualitative approach has support in interviews of managers, teachers and students. For consideration of these representations, the theoretical-methodological support in Depth Hermeneutics (THOMPSON, 1995). It is emphasized the importance of the contribution of Pierre Bourdieu (2007, 2008, 2011, and 2012) due, not only to the indispensable application of both his methodological stance, as guaranteed by the theoretical resource categories of Habitus, Cultural, Social and Economic Capital, Symbolic Violence and Symbolic Power as well as Social Space and Field. It is exposed the socio-historical scenario in which was established the Bachelor in gastronomy, including the managers speech, showing the mission of the course, the initial difficulties for its implantation and the current debate about its social function. Similarly, it is proposed an analysis about the current Pedagogical political project, highlighting its curriculum vocation. Subsequently, it is presented the experience of the first cycle of bachelor’s degree from the teaching point of view, understanding the conceptions of gastronomy itself as an area of knowledge, the theoretical and methodological challenges, and the construction of a teaching identity and the training itinerary of this teacher. Finally, it is showed the perspective of a group of bachelor's degree students from a reflexive itinerary about the centralities of such academic formation trajectory, the academic marks and the repercussions of that experience in the life of undergraduate students. In this picture, you can see that some of the problems are really hard to get immediate resolution. The structural issue – represented by waiting for the completion of the building for the course of gastronomy at the Institute of Cultural and art-ICA and for the bureaucratic difficulties for the acquisition of inputs for the practical classes as well as the consolidation of a teacher training still remain as points of tension. Other sensitive predicaments, pointed by the actors of this study, however, relate to curricular adjustments and methodological postures, which may begin to be eased with the mere admission of its limitations. The advice to persevere at the University in spite of the initial difficulties and challenges - recommendation which seemed somewhat unreasonable to students in 2010, currently stands in need of affirmation of Gastronomy at the Academy and in search of recognition and professional appreciation of this Bachelor. The genesis of the course, itself, has brought to the University a new perspective of knowledge, expanding the meaning of the study on feeding. This scholarly statement has begun to rewrite the dynamics of the gastronomic market in the state of Ceará, which, due to the existence of those bachelor’s degree students and professors, has been forced to confront the cuisine not only by its character of refinement of cooking or cutting techniques, but also by the realization that the gourmet understands far beyond the substance on the plate.